Equivalence of closed 1-forms on surfaces with edge - Budnyts'ka, T. V.; Prishlyak, O. O. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We investigate closed 1-forms with isolated zeros on surfaces with edge. A criterion for the topological equivalence of closed 1-forms is proved.